KUALITAS AIR SUNGAI MARON DENGAN PERLAKUAN KERAMBA IKAN DI KECAMATAN TRAWAS KABUPATEN MOJOKERTO JAWA TIMUR - Sasi Gendro Sari (Universitas Lambung Mangkurat, 2007)
The aims of this research were to assess water quality of Maron river and to study the relationship between water quality of the river and breeding of fish in keramba. Chemical and physical parameters observed were water temperature, conductivity, water acidity, dissolved oxygen, total suspended solid and total organic matter. The parameters were compared to water quality standard issued by The Government of East Java Province. The results showed that breeding of fish in keramba reduced water quality of Maron river by increasing total suspended solid and total organic matter of the water.